Fe3Pt intermetallic nanoparticles anchored on N-doped mesoporous carbon for the highly efficient oxygen reduction reaction. Issue 36 (1st April 2020) - Chen, Danke; Li, Zhuoyi; Zhou, Yu; Ma, Xu; Lin, Hanqing; Ying, Wen; Peng, Xinsheng
Abstract : N-Doped mesoporous carbon catalysts dispersed with Fe3 Pt intermetallic nanoparticles, exhibiting excellent ORR performance, were synthesised by direct pyrolysis of Pt–Fe co-functionalized ZIF-8. Abstract : A facile strategy is proposed to prepare N-doped mesoporous carbon catalysts dispersed with Fe3 Pt intermetallics (Fe3 Pt/N@C) through direct pyrolysis of Pt–Fe co-functionalized ZIF-8. The catalysts exhibit excellent ORR activity, outstanding mass activity with ultralow Pt loading, low H2 O2 yield, and high cycling stability in alkaline medium.